Value of the injection site counting and IV line in DMSA renal scintigraphy - Balci, TA; Ciftci, I (Springer, 2004)
[Abstract Not Available]
17th Annual Congress of the European-Association-of-Nuclear-Medicine -- SEP 04-08, 2004 -- Helsinki, FINLAND